Chemical investigation of Corypha taliera Roxb - Shoeb, Mohammad; Nusrat, Shefat E; Khondker, Moniruzzaman (Bangladesh Journal of Botany, 2013)
?-sitosterol was isolated by silica gel column chromatography from the dichloromethane soluble extract of pericarp of Corypha taliera Roxb. (Talipalm), a rare species of Arecaceae family. The compound was characterized by IR, 1H and 13C NMR spectroscopic studies. Fatty acid compositions of oil of the pericarp was determined as their methyl esters and identified by gas chromatography having flame ionization and the gas chromatograph was coupled to mass spectroscopic detectors. Myristic, palmitic, oleic, linoleic, stearic, arachidic and lignoceric acids were found to be present in the oil. The palmitic acid was predominant (50.75%) in the oil. The relative percentage of unsaturated acid i.e., linoleic and oleic acids was found to be 15.58 and 20.89%, respectively. DOI: http://dx.doi.org/10.3329/bjb.v42i1.15824 Bangladesh J. Bot. 42(1): 51-53, 2013 (June)